Design And Analysis Of A Double Carrier Modulation/Differential Detection Technique For Optical Fiber Communications - Matrood, Naseer Abbas (2003)
Fiber optic long haul transmissions have been globally deployed at a staggering rate. All of the installed networks are using Intensity Modulation/Direct Detection (IM/DD). Although the IM/DD systems are proven and used widely, these networks are still subjected to many problems. The main problems associated with long haul transmission are; high dispersion and losses incurred by the fiber, and the inability of the receiver circuit to regenerate the transmitted bits. This is because of low signal power and inter-symbol interference, in addition to the masking noises. The recovery technique in the conventional receivers based on the IM/DD scheme uses an injected voltage level as a threshold into a decision circuit, which decides whether the incoming bit is a 0 or a 1. This scheme has two inherent problems; the instability of the injected threshold voltage, and the complexity of a dynamic threshold processing. As the threshold voltage has its own noise and fluctuation, it adds to the deterioration of the signal, thus limits the systems performance. Meanwhile, due to the random nature of the incoming bits, coupled with the masking noises and jitters, the threshold voltage level cannot be set at a fixed value, and therefore a dynamic voltage threshold adjustment is required. The demand of high data rate and long transmission distance impose much difficulty, therefore new approaches and techniques have to be applied to improve the system and solve these problems. This led to the development of new techniques for the system performance improvement.